Konseling Individu Teknik Asssertive Training untuk Meningkatkan Perilaku Asertif Siswa - Kartini Friatny (Jurnal Pendidikan Dasar dan Menengah (Dikdasmen), 2025)
The purpose of this study was to describe individual counseling services with Assertive Training techniques on assertive behavior in students of SMK Negeri 7 Makassar. This research uses a qualitative descriptive method. Data collection is taken from the results of interviews, observations and documentation. The subject of this research is one of the X class students of SMK Negeri Makassar whose initials are AA and identified as having low assertive behavior, then data analysis is carried out by data reduction, data presentation and drawing conclusions. The results of individual counseling research conducted in this case using Assertive Training techniques, I as a counselor and counselee design and determine situations where the counselee feels difficulty in conveying assertive behavior. The situation described must be clear and detailed, so that the counselee can describe and explain what he is facing in reality. The counselor provides input and encouragement to the counselee especially on facial expressions, body posture, tone of voice, eye contact, and so on. I also give homework to the counselee as a behavioral target to be achieved, and finally a discussion regarding the results achieved by the client is carried out during the next meeting. The results showed that individual counseling services using Assertive Training techniques can be used to improve assertive behavior in students.